Streetwise for book smarts : grassroots organizing and education reform in the Bronx - Su, Celina, 1977- (Ithaca : Cornell University Press, 2009)
Annotation In Streetwise for Book Smarts, Celina Su examines the efforts of parents and students who sought to improve the quality of education in their local schools by working with grassroots organizations and taking matters into their own hands. In these organizations, everyday citizens pursued not only education reform but also democratic accountability and community empowerment. These groups had similar resources and operated in the same political context, yet their strategies and tactics were very different: while some focused on increasing state and city aid to their schools, others tried to change the way the schools themselves operated. Some coalitions sought accommodation with administrators and legislators; others did not. The events Su describes began with a series of stabbings in Bronx high schools during the 2003-2004 school year. After this rash of violence, several grassroots groups cited the need for additional safety patrols. Mothers from one school spoke of how they had previously protested until they got extra officers, a fairly scarce resource in New York public schools, at their local elementary school. Others asserted that not all the safety patrol officers already in place were treating students humanely. Parent organizations and school officials battled over who was to blame for the school violence. Did a police presence solve the problem, or did it exacerbate the schools' violence-prone conditions? Members of different groups proposed and mobilized behind a range of remedies. These divergent responses shed light on the ways in which the choices made by each organization mattered. By learning from Su's close observation of four activist groups in the Bronx, including Mothers on the Move and Sistas and Brothas United, we can better understand strategies that may ultimately lead to better and safer schools everywhere and help to revitalize American democracy.
A kaleidoscope of people power -- Public education and organizing in the Bronx -- Organizing the organizations : the Alinskyite tool kit -- Friends forever : the Freirean tool kit -- Off the charts : tackling issues of race in SCOs -- What these tools can build : developing capacities for policy making -- Favorite hits : embedded preferences for confrontation or collaboration -- Commitment and commencement.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: School improvement programs -- New York (State) -- New York -- Case studies; Educational change -- New York (State) -- New York -- Case studies; Community organization -- New York (State) -- New York -- Case studies; Nonprofit organizations -- New York (State) -- New York -- Case studies; Social movements -- New York (State) -- New York -- Case studies; Community and school -- New York (State) -- New York; Bronx (New York, N.Y.) -- Social conditions; Enseignement -- Réforme -- New York (État) -- New York -- Études de cas; Organisation communautaire -- New York (État) -- New York -- Études de cas; Associations sans but lucratif -- New York (État) -- New York -- Études de cas; Mouvements sociaux -- New York (État) -- New York -- Études de cas; Relations école-collectivité -- New York (État) -- New York; EDUCATION -- Educational Policy & Reform -- General; Community and school; Community organization; Educational change; Nonprofit organizations; School improvement programs; Social conditions; Social movements; New York (State) -- New York; New York (State) -- New York -- Bronx; Case studies